APPLICATION OF CONSTITUTIVE MODELS IN THE VOLCANIC TEPHRA “TIERRA BLANCA JOVEN” - Chavez Hernandez, Jose Alexander (Universidad de Costa Rica, 2014)
The volcanic tephra Tierra Blanca Joven (TBJ) covers most of the Metropolitan Area of San Salvador where problems of mass wasting problems occur. To understand its behavior the Mohr-Coulomb, Modified Cam Clay and Hypoplasticity constitutive models were used to simulate consolidation and triaxial tests; looking for the one closer to real laboratory results. The constitutive models are used into finite element software to simulate the behavior of a soil mass (slope stability, bearing capacity etc.). Shear box, drained triaxial and consolidation tests were made in order to obtain the parameters for the models. The soil must be either saturated or dry, otherwise unsaturated properties are needed. After comparing the results of the constitutive model it was observed that none of them display exactly the real behavior observed in the laboratory. Mohr-Coulomb is the model that is used in all the geotechnical studies in El Salvador and it was the model that showed more deficiencies. Hypoplasticity showed good results in the triaxial tests but deviated from reality in the consolidation results. The results indicate that a different constitutive model and lab equipment are necessary (as TBJ is an unsaturated soil) to characterize the behavior of the soils in El Salvador.